2022
DOI: 10.1088/2053-1591/ac871f
|View full text |Cite
|
Sign up to set email alerts
|

The effect of synthesis route on the photocatalytic performance of Ag-TiO2 using rhodamine b dyes, pesticides, and pharmaceutical waste as model pollutants

Abstract: The use of noble metal loading such as Ag to improve the photocatalytic performance of TiO2 has been well studied. Though different synthesis methods have been used to synthesize Ag-TiO2 nano-composite, the effect of the different synthesis routes on the photocatalytic performance has not been studied and compared. This study focusses not only on the enhancement of photocatalytic performance by the addition of Ag, but also on the influence of the synthesis process on photocatalytic performance. Two different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The g-C3N4 was prepared by calcining 20 g of melamine with high temperature muffle furnace at 550 °C; (1) Weighing a fixed ratio of TiO2, g-C3N4, Bi(NO3)3-5 NaH2PO4-2H2O, where the ratio of g-C3N4 and BiPO4 masses was a constant 1:5, chan only the mass fraction ratio of TiO2 in the catalyst [40]. Deionized water was added fo trasonic stirring, followed by washing the solution in small amounts into the Teflon b (the solution in the bottle did not exceed 80% of the total capacity of the Teflon bottle Subsequently it was placed in a hydrothermal reactor for 8 h at 160°; after extraction, dr and grinding to obtain 5 wt%, 7.5 wt%, 10 wt%, 12.5 wt%, 15 wt%, and 17.5 wt% Ti-BPC Weigh an appropriate amount of g-C3N4 and add an appropriate amount of Bi(NO3)3-5 with NaH2PO4-2H2O with ultrasonic stirring to form suspension; subsequently placed hydrothermal reactor at 160° for 6 h [42]; the precursor complex g-C3N4/BiPO4 was obta as a white solid, an appropriate amount of MnCl2 dissolved in deionized water was ad the mixed solution was poured into the autoclave, sealed and compacted in an oven at for 8 h; 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, and 30 wt% of Mn-BPC, respectively.…”
Section: Preparation Of Composite Photocatalystmentioning
confidence: 99%
See 1 more Smart Citation
“…The g-C3N4 was prepared by calcining 20 g of melamine with high temperature muffle furnace at 550 °C; (1) Weighing a fixed ratio of TiO2, g-C3N4, Bi(NO3)3-5 NaH2PO4-2H2O, where the ratio of g-C3N4 and BiPO4 masses was a constant 1:5, chan only the mass fraction ratio of TiO2 in the catalyst [40]. Deionized water was added fo trasonic stirring, followed by washing the solution in small amounts into the Teflon b (the solution in the bottle did not exceed 80% of the total capacity of the Teflon bottle Subsequently it was placed in a hydrothermal reactor for 8 h at 160°; after extraction, dr and grinding to obtain 5 wt%, 7.5 wt%, 10 wt%, 12.5 wt%, 15 wt%, and 17.5 wt% Ti-BPC Weigh an appropriate amount of g-C3N4 and add an appropriate amount of Bi(NO3)3-5 with NaH2PO4-2H2O with ultrasonic stirring to form suspension; subsequently placed hydrothermal reactor at 160° for 6 h [42]; the precursor complex g-C3N4/BiPO4 was obta as a white solid, an appropriate amount of MnCl2 dissolved in deionized water was ad the mixed solution was poured into the autoclave, sealed and compacted in an oven at for 8 h; 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, and 30 wt% of Mn-BPC, respectively.…”
Section: Preparation Of Composite Photocatalystmentioning
confidence: 99%
“…(2) Weigh an appropriate amount of g-C 3 N 4 and add an appropriate amount of Bi(NO 3 ) 3 -5H 2 O with NaH 2 PO 4 -2H 2 O with ultrasonic stirring to form suspension; subsequently placed in a hydrothermal reactor at 160 • for 6 h [42]; the precursor complex g-C 3 N 4 /BiPO 4 was obtained as a white solid, an appropriate amount of MnCl 2 dissolved in deionized water was added, the mixed solution was poured into the autoclave, sealed and compacted in an oven at 160 • for 8 h; 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, and 30 wt% of Mn-BPC, respectively.…”
Section: Preparation Of Composite Photocatalystmentioning
confidence: 99%
“…Another major limitation of dispersants is their inability to remediate the water-soluble components of crude oil in the marine environment. The observation over the years is that water-soluble portions of hydrocarbons from spilled oil stay in the marine ecosystem for several years, wreaking damaging effects on the oceans with a causal sequence on the economy and well-being of the inhabitants in the areas where crude oil spill occurs. , On the other hand, the effectiveness of photocatalysis in degrading pollutants that are water-soluble, such as dyes, pesticides, and pharmaceutical wastes has been reported. …”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, for instance, the daily solar irradiation varies between 4 and 6.5 kWh/m 2 /day, emphasizing the advantage of optimizing TiO 2 for utilization of this valuable resource. Furthermore, the presence of Ag nanoparticles on the TiO 2 surface acts as an electron sink, effectively capturing photogenerated electrons from the conduction band of the adjacent semiconductor, owing to the Fermi level gradient. , Numerous research studies have demonstrated the remarkable photocatalytic degradation capabilities of Ag-TiO 2 for various environmental organic pollutants. ,,, In a recent study, Nyankson et al systematically explored the Ag composition in Ag-TiO 2 , revealing that the photocatalytic performance peaks with 0.5 wt % Ag incorporation . Ag-TiO 2 can be synthesized through various methods, including wet impregnation, sol–gel, coprecipitation, hydrothermal, and photo deposition techniques. In our current research, we have chosen to employ the photodeposition method to modify TiO 2 with silver (Ag).…”
Section: Introductionmentioning
confidence: 99%